Modernising education: unlearned lessons from Frederick Taylor - Shulga, Marina A.; Poperechna, Galyna A.; Kondratiuk, Liubov R.; Petryshyn, Halyna R.; Zubchyk, Oleh A. (Linguistics and Culture Review, 2021)
Nowadays, the term “modernisation” is usually associated with the term “digitalisation”, which, in its turn, is adopting semantics of the terms “modern”, “progressive”, “future”. Frederick Taylor was one of the first scholars to face the limits of the latter and came close to a number of questions concerning their boundary indicators, content characteristics and guidelines for their establishment. Nowadays, these unexplained questions tend to disguise themselves as something “inevitable”, “obvious”, “insurmountable” in the educational process. The methods of an integrated approach allowed for demonstrating that the understanding of the content of the so-called “unlearned lessons” from Frederick Taylor regarding the problem of “human capacity” in terms of its mental component can help sufficiently in finding an answer to the question about the ways of developing critical thinking among the inhabitants of this space, and about the specific “trivium” and “quadrivium” for them. Therefore, it was concluded that the problem of “human capacity” is crucial for the development of the ideology of education as a system of ideas about the role and purpose of education in society, and, thus, about what is an “educated person” and how it is possible to create one today.